ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PENGIRIMAN PRODUK ARNOTTS KE ALFAMART AREA JABODETABEK DAN BANTEN PT INTAN UTAMA LOGISTIK TAHUN 2015 - Haryono Haryono; Lia Mulia Sari (Institut Transportasi dan Logistik Trisakti, 2016)
PT Intan Utama Logistics is a company engaged in the field of freight forwarding that its main task, delivering goods using multiple modes of transportation available. As a freight forwarding service company PT. Intan Utama Logistik should be able to provide the best services to meet the needs of customers, one of which is in terms of timeliness of delivery of goods safely reach the destination because it can affect the level of customer satisfaction. But in fact in the process of delivery of goods are still common problems, such as delays in delivery caused by various factors, including wage service trips within the scope of delivery, a factor congestion on land and the diversion of traffic flows, frequent damage to the fleet operational, operational fleet is not in accordance with the needs and the goods component is lacking. This study aims to determine the factors that cause delays in shipping products to alfamart Arnotts Greater Jakarta and Banten area at PT Intan Utama Logistik Year 2015. To find out the root of the problem of delays in shipping products to alfamart Arnotts Greater Jakarta and Banten area and the solution at PT. Intan Utama Logistik Year 2015. To find out effective measures or solutions in addressing delays in shipping products to alfamart Arnotts Greater Jakarta and Banten area at PT. Intan Utama Logistik Year 2015. The data analysis techniques used by the author is a fishbone diagram or cause-effect diagram ,. the writer has the conclusions that can be drawn as follows: (1) Total shipments (shipment) the PT Intan Utama Logistik in 2015 amounted to 9280, goods were delivered (delivery) amounted to 7868 and the total of goods that experienced delays amounted to 1410 with the performance results achieved by 15:19%. (2) Analysis of the root cause of the problem is known 10 variables rated by the respondents there are four variables that have problems with the average - average percentage of problematic factor is> 43.66%. The four variables are problematic, namely Machines, Methods and Money. (3) Having found a major problem in this problem, there are several factors that cause delay that disbursement of funds should wait for the decision of GM, the number of operational fleet is used to handle distribution activities are limited, the whole process delivery of goods should use transport fleet and has become a liability to determine for courier service.